Sensory Impairment and Health-Related Quality of Life - Hye-Jin KWON; Ji-su KIM; Yoon-jung KIM; Su-jin KWON; Jin-Na YU (Tehran University of Medical Sciences, 2015)
Background: Sensory impairment is a common condition that exerts negative effects on health-related quality of life (HRQoL) in the elderly. This study aimed to determine the relationship between sensory impairment and HRQoL and identify sensory-specific differences in the HRQoL of elderly. Methods: This study used data from the Korean National Health and Nutrition Examination Survey V (2010-2012), analyzing 5,260 subjects over 60 years of age who completed ophthalmic and otologic examinations. Vision and hear-ing impairment were measured and classified. HRQoL was determined according to the European QoL five dimen-sion test (EQ-5D). Multivariate logistic regression analysis and analysis of covariance were performed to identify rela-tionships between sensory impairment and HRQoL dimensions as well as differences in HRQoL scores. Results: In the final adjusted multivariate model, there was a statistically higher proportion of those with dual sensory impairment who reported problems with mobility (adjusted odds ratio [aOR] 2.30, 95% confidence interval [CI] 1.45-5.03), usual activities (aOR 2.32, 95% CI 1.16-4.64), and pain/discomfort among EQ-5D subcategories (aOR 1.79, 95% CI 1.07-2.97). In the EQ-5D dimensions, the means and standard deviations of vision impairment (0.86 [0.01]) and dual sensory impairment (0.84 [0.02]) appeared meaningfully lower than those for no sensory impairment (0.88 [0.00]) or hearing impairment (0.88 [0.01]); P = .02). Conclusion: Sensory impairment reduces HRQoL in the elderly. Improvement of HRQoL in the elderly thus requires regular screening and appropriate management of sensory impairment.